The Effect of a Skin Barrier Film on the Incidence of Dressing‐Related Skin Blisters After Spine Surgery. (29th June 2020) - Cole, Maryanne; Smith, Isabel; Vlad, Steven C.; Golenbock, Samuel W.; Sorrentino, Kerry
ABSTRACT: Tension blisters from adhesive dressings may lead to pain and delayed surgical wound healing for surgical patients and cause an institutional cost burden. Commercial skin barrier film products may reduce dressing‐related postoperative skin blistering in surgical patients. Project investigators at an orthopedic specialty hospital randomized 185 surgical spine patients to receive either a standard wound dressing (ie, control group) or a dressing with the addition of a skin barrier film applied beneath it (eg, treatment group). During the first postoperative dressing change, the participants' skin was assessed for redness, soreness, blistering, or tearing. Approximately 15% of participants in the treatment group and 15% of participants in the control group developed a postoperative skin injury ( P = .98). Multivariable analyses did not indicate the skin barrier film provided a protective effect. Additionally, there was no association between patient‐specific characteristics and skin blisters among the participants. These results do not support the use of a skin barrier film in surgical spine patients.